THE EFFECT OF BREASTFEEDING EDUCATION AMONG POSTPARTUM MOTHERS ON EXCLUSIVE BREASTFEEDING PRACTICE ONE MONTH AFTER DELIVERY - Laurentius Juan Wicaksono; Dimas Tri Anantyo; Julian Dewantiningrum; Bambang Hariyana (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background: Exclusive breastfeeding is a standart of care for newborn. In 2017 within area of Semarang City, only 19,5% women who practiced exclusive breastfeeding .One of the problems was low level of mother’s knowledge because lack of breastfeeding education especially by the health services institutions. The aim of the study is to asses the effect of breastfeeding education among postpartum mothers on exclusive breastfeeding practice in one month after delivery. Method: A quasi experimental study design was conducted among postpartum mother in purposively selected health institutions of Semarang city. All eligible women were placed into intervention (n=25) and control (n=25) group. The intervention group received standart education with educational media and control group received standart education only which lasts for 15 minutes. Data were collected through interviewer-administered questionnaire at one month after education session. Results: The number of mothers who practiced exclusive breastfeeding for a month was greater in intervention group than the control group (p=0,025). The level of knowledge also greater in intervention group (p=0,016). Also, there were no significant relationship between age, working status, maternal parity and exclusive breastfeeding while there was significant relationship between maternal education and exclusive breastfeeding practice. Conclusion: Breastfeeding education with educational media increases the mother’s knowledge about exclusve breastfeeding and practice of exlusive breastfeeding up to 1 month.